Climate Change Impacts on Atlantic Oceanic Island Tuna Fisheries - Townhill, Bryony L.; Couce, Elena; Bell, James; Reeves, Stuart; Yates, Oliver (Frontiers in Marine Science, 2021)
Climate change is already affecting the distributions of marine fish, and future change is expected to have a particularly large impact on small islands that are reliant on the sea for much of their income. This study aims to develop an understanding of how climate change may affect the distribution of commercially important tuna in the waters around the United Kingdom’s Overseas Territories in the South Atlantic. The future suitable habitat of southern bluefin, albacore, bigeye, yellowfin and skipjack tunas were modelled under two future climate change scenarios. Of all the tunas, the waters of Tristan da Cunha are the most suitable for southern bluefin, and overall, the environmental conditions will remain so in the future. Tristan da Cunha is not projected to become more suitable for any of the other tuna species in the future. For the other tuna species, Ascension Island and Saint Helena will become more suitable in the future, particularly so for skipjack tuna around Ascension Island, as the temperature and salinity conditions change in these areas. Large marine protected areas have been designated around the territories, with those in Ascension and Tristan da Cunha closed to tuna fishing. Although these areas are small relative to the whole Atlantic, these model projections could be useful in understanding whether this protection will benefit tuna populations into the future, particularly where there is high site fidelity.